Environmental Impact Evaluation of Tofu Production using Life Cycle Assessment - Lestari, Rizka; Rahmawati, Dian; Binti Ibrahim, Khairul Nadiah (Politeknik Negeri Malang, 2024)
Tofu is one of the products made from soybeans that a sizable portion of people in a larger society consume. There are several ways to make tofu, from conventional to modern. The conventional tofu production process generates a lot of waste. Many of the researchers have explored numerous strategies to handle tofu waste in a way that minimizes its harmful influence on the environment. However, in many cases, the environmental impact is simply transferred from one process to another during the treatment of tofu waste. As a result, the whole tofu-making process requires an evaluation of the effects. Among these approaches is life cycle assessment (LCA). The study discovered that energy use was the primary factor leading to environmental impacts. Burning firewood for energy resulted in 55.61 kg of carbon dioxide equivalent. The emission value has been reduced to 32 kg CO₂ eq and 28 kg CO₂ eq, respectively, according to the findings of simulations by utilizing biogas and natural gas as fuels.